TINJAUAN SISTEMATIS: INTEGRASI DISCOVERY LEARNING DAN VIRTUAL REALITY UNTUK MENGEMBANGKAN BERPIKIR KRITIS DALAM PEMBELAJARAN IPA DI SEKOLAH DASAR - Sarry Sumiyaty; Ucu Rahayu; Ika Lestari (Program Studi Pendidikan Guru Sekolah Dasar FKIP Universitas Pasundan, 2025)
The rapid development of digital technology has created new opportunities for science learning in primary schools, particularly in fostering students’ critical thinking skills. However, science education at the elementary level is still often dominated by conventional methods that emphasize rote memorization, leaving students with limited opportunities to develop analytical and reflective abilities. This study aims to examine the potential of integrating the Discovery Learning (DL) model with Virtual Reality (VR) technology to enhance critical thinking skills in science learning. The methodology employed is a literature review involving a systematic analysis of articles, research reports, and academic publications related to DL, VR, and science education. The review focuses on identifying contributions, advantages, and limitations of applying VR within the context of primary education. Findings indicate that the integration of DL with VR has the potential to provide immersive, interactive, and contextual learning experiences, encouraging students to observe, ask questions, and evaluate information critically. While VR enables the tangible exploration of abstract scientific concepts, DL facilitates inquiry and independent discovery processes. Nevertheless, its implementation faces challenges such as limited infrastructure, the need for teacher training, and the relatively high cost of technological devices. Overall, this review highlights that the use of VR within a DL framework can serve as an innovative strategy to strengthen students’ critical thinking skills. Recommendations are directed at teachers to begin exploring technological integration, policymakers to support the provision of facilities, and researchers to further investigate its effectiveness through empirical studies in primary school settings